2017
DOI: 10.3389/fmed.2017.00099
|View full text |Cite
|
Sign up to set email alerts
|

Complement in Non-Antibody-Mediated Kidney Diseases

Abstract: The complement system is part of the innate immune response that plays important roles in protecting the host from foreign pathogens. The complement components and relative fragment deposition have long been recognized to be strongly involved also in the pathogenesis of autoantibody-related kidney glomerulopathies, leading to direct glomerular injury and recruitment of infiltrating inflammation pathways. More recently, unregulated complement activation has been shown to be associated with progression of non-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…The complement system is part of the innate immune response with the main function of protecting the host from foreign pathogens [17][18][19]. The complement cascade is activated by the lectin pathway, the classical pathway and the alternative pathway, all of them converging on an enzymatic multimeric protein complex, the C3 convertase [18].…”
Section: Complement Systemmentioning
confidence: 99%
“…The complement system is part of the innate immune response with the main function of protecting the host from foreign pathogens [17][18][19]. The complement cascade is activated by the lectin pathway, the classical pathway and the alternative pathway, all of them converging on an enzymatic multimeric protein complex, the C3 convertase [18].…”
Section: Complement Systemmentioning
confidence: 99%
“…Increasing evidence has been accumulated showing that complement activation is implicated in the pathogenesis of different non-antibody-mediated glomerular diseases and in the general progression of renal disease, regardless of the initial insult (Angeletti et al, 2017). Complement proteins are a major constituent of the urine of proteinuric patients (Proteinuria is a strong predictor of progression in CKD).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, studies in rodent knockout showed that the absence of C3aR and C5aR on renal tubular epithelial cells or circulating leukocytes attenuated renal IRI. Treatment in vivo using antagonist for C3aR and C5aR and for factor B could improve graft survival, reducing the decrease in renal injury, tubular apoptosis, and inflammation (216,220,221).…”
Section: Cell-specific Effects Of Complement In Aki-to-ckd Transitionmentioning
confidence: 99%